Motivators and Demotivators for Employees - Rosłon, Jolanta (Olsztyn Economic Journal, 2020)
Employee motivation is the basis of effective human resource management. A properly designed motivational system and an adequate selection of motivation drivers elicit employee behaviour desirable from the employer’s standpoint and thus play a decisive role in the organisation’s success. This study aimed to identify factors that have a motivating and demotivating effect on the workforce, as well as to determine the motivational intensity of selected incentives. The empirical research also covered the influence of conflicts – interpersonal and intrapersonal – on the motivation levels among the employees, and the effectiveness of motivational systems applied in the organisations. The findings were obtained through a Web study (CAWI) conducted with the use of a survey questionnaire distributed by electronic means. According to the respondents, the most effective motivation driver is the level of remuneration. This factor is a priority mainly for people with a lower income, lower status and shorter work experience. A positive atmosphere at the workplace turns out to be the second most important driver, whereas non-financial benefits rank third. Furthermore, the poll demonstrates that the level of employee motivation is largely affected by conflicts between employees, employees and their managers, or those of an internal nature. Irrespective of their character and development, antagonisms generate a slew of negative consequences, such as weaker engagement in the job, increased staff fluctuation, a drop in work efficiency and the manifestation of unfavourable attitudes among staff members.